Managerial calculations from the viewpoint of logic, analysis microeconomics and other theoretical disciplines - Hašková, Simona, 1973- (2015)
It is no secret that 'managerial' solutions are not, on average, nearly as reliable as 'technical' solutions. The focus of this work is to clarify the reasons why this is so, and to seek ways to increase the reliability of managerial solutions. The causes of this situation are both subjective (human factor failure), which can be influenced, and objective (complexity of the problem, the specifics of human behaviour, etc.) that can be only minimally influenced. Significant subjective causes at work were identified as: a. cognitive distortions at the mental level of thinking of the problem solvers; b. deficiencies in making inference and drawing conclusions; c. incorrect argumentation. There are two ways to reduce these causes: 1. cultivation of managerial thinking of the problem solvers; 2. the use of reserves in the implementation of approaches and tools of theoretical disciplines that already operate successfully elsewhere and are beneficial for managerial solutions. The first way deals with procedures for managerial solutions formulated in the language of the relevant discipline (the language of management), expressed by natural language and the chain of formulas (calculations) and visual (graphic) tools in the form of managerial decision trees, diagrams and charts with the rules of 'managerial logic'. This is generally defined as a set of approaches, tools, methods and skills needed for credible justification when solving managerial problems.